Association between dietary patterns, symptoms of depression and self-rated health in adults in Iceland. The Saga Cohort pilot study - Lísa Hafliðadóttir 1991- (2023)
Aim: The aim of this cross-sectional study was to investigate the association between dietary patterns, symptoms of depression and self-rated health in Icelandic adults. Method: Cross-sectional data from the 2014 Stress and Gene Analysis (SAGA) cohort pilot study were used in this study. Participants, all from the capital area, completed validated questionnaires on dietary habits with dietary patterns identified using a principal component analysis. Two major dietary patterns were discovered with eigenvalue above one and were classified as healthy dietary pattern and unhealthy dietary pattern. Participants were divided into tertiles according to their adherence to these patterns. Depressive symptoms were measured using the Patient Health Questionaire-9 (PHQ-9). Participants who scored 10 or more points in the questionnaire were classified as having depressive symptoms. Self-rated health was assessed using a question where participants were asked to rate their health on a scale from 0 to 100; 0 indicating worst possible health and 100 indicating best possible health. Participants scoring their health at 37 or lower were classified as having poor self-rated health. Binary logistic regression was used to measure the association between dietary patterns and depressive symptoms and self-rated health. Adjustments were made for sex, age, education, physical activity, body mass index and smoking habits. The analyses were also stratified by sex. Results: Data from 802 adults was used in this study (mean age = 49 years; 55% women). In total, 56 participants (7%) reported having symptoms of depression and 49 participants (6%) estimated their health as poor. In an adjusted model, those with the highest adherence to an unhealthy dietary pattern were more than two times more likely to report depressive symptoms (OR 2.19, 95% CI 1.16-4.15) than participants with lower adherence. High adherence to unhealthy dietary pattern was not statistically associated with poor self-rated health (OR 1.47, 95% CI 0.68-3.09). When stratified ...